Influence of indoor environmental quality on work productivity in green office buildings: A review - Esfandiari, M.; Zaid, S.M.; Ismail, M.A.; Aflaki, A. (2017)
Indoor Environment Quality (IEQ) of green offices is able to change occupants' behaviour by representing various conditions. The IEQ depends on factors such as lighting, noise, thermal quality, and air quality which directly or indirectly influence the occupants' behaviour and work productivity. To improve and support the work productivity of occupants, it is significant to consider occupants' physical condition, well-being and psychological facets which are affected by IEQ. Consequently, it is essential to understand initially the most effective IEQ factors that impact on occupants' behaviour and the overall satisfaction. Occupant's satisfaction can be improved by elimination or minimization factors that cause any discomfort, illness or dissatisfaction. However, most research on IEQ and occupant satisfaction are focused on conventional commercial and office buildings. There is a lack of research evaluating the performance and IEQ levels of new "green" buildings, in relation to work productivity. Thus, the current study reviews peer-reviewed journal articles and dissertations to find crucial factor influences on IEQ and work productivity in "green" offices. The results showed that increasing the quality of IEQ factors will most likely enhance occupant's productivity, which directly brings benefits for companies. Through a critical literature review, the study found that Indoor Air Quality (IAQ) is the most influential, which is vital for enhancing work productivity and it can boost occupants' satisfaction. Moreover, occupants' personal control over thermal condition shows the huge effect on enhancing work productivity. The results showed that there is a lack of a comprehensive study to rank the IEQ factors which effect on work productivity.